Inorganic Solid‐State Electrolytes in Potassium Batteries: Advances, Challenges, and Future Prospects - Titus Masese; Godwill Mbiti Kanyolo (ChemElectroChem, 2025)
Abstract Potassium‐ion batteries (KIBs) are increasingly attractive owing to their high voltage and projected low cost. However, the advancement of KIBs has been constrained by challenges related to electrolyte stability and interface compatibility. Traditional liquid electrolytes pose significant risks, including leakage and flammability, prompting a shift towards solid‐state electrolytes, which offer improved energy density, safety and thermal stability. This Perspective explores the current state of inorganic solid‐state electrolytes entailing oxides, chalcogenides, halides and hydrides. We delve into their recent advancements, identifying key challenges and future research opportunities, with the aim of advancing the development of high‐performance all‐solid‐state potassium batteries.